“…We do not know, who are they, where are they from and what are their aims”. The Mongol Expansion in the Light of Published Latin Sources - F.N. Veselov; A.V. Maiorov (Золотоордынское обозрение)
This article is primarily dedicated to the monograph of R. Hautala “From ‘David, King of the Indies’ to ‘Detestable Plebs of Satan’: An Anthology of Early Latin Information about the Tatar-Mongols”. One can find that this anthology is the most complete collection of Latin sources, which were created before the Mongol invasion of the European states and concerning the Mongols, their genesis and aims of the Western campaign. The authors state that the mentioned study includes not only the high-level presentation of handwritten artifacts, but extensive research, providing a number of original and decisive conclusions as well. On the other hand, the authors of the paper mention complexes of sources, which could provide more detailed image of diplomatic relations between European monarchs and heads of the Mongol armies, Christian interpretations of threating and unknown enemy who unexpectedly appeared on the boarders of Catholic world. Particularly, the authors point on the fragment from Alberic of Trois-Fontaines, which could be described not only as a source on the Russian-Mongol battle, as well as on the sources on diplomatic relations between the Holy Roman Empire and Mongol rulers, Russian sources that had own impact on the European scholars’ eschatological interpretations of the Tatar invasion.